Analisis Laporan Perubahan Modal Konsolidasian PT. Dharma Samudera Fishing Industries, Tbk - Anik Nurmawati; Eka Safitri; Nyimas Dyah Puspitasari; Tyas Anatasya Febrianti; Diajeung Suci Rahayu (Universitas 45 Surabaya, 2024)
This research examines the consolidated capital change report of PT Dharma Samudera Fishing Industries, Tbk through secondary data obtained from IDX using data collection techniques, namely searching, reading, understanding and reviewing data and theories contained in books, literature, journals, standard statements financial Accounting. It was found that there are differences in the amount of equity which will increase in 2022. The results of this research show that the company has been quite transparent and inclusive, covering changes in the amount of equity.